Enabling geospatial context in an iot decentralised reputation management system using ethereum smart contracts - Weerapanpisit, Ponlawat (2021)
Weerapanpisit, P., Trilles, S., Huerta, J., & Painho, M. (2021). Enabling geospatial context in an iot decentralised reputation management system using ethereum smart contracts. In 2021 IEEE International Conference on Omni-Layer Intelligent Systems, COINS 2021 (pp. 1-6). (2021 IEEE International Conference on Omni-Layer Intelligent Systems, COINS 2021). Institute of Electrical and Electronics Engineers Inc.. https://doi.org/10.1109/COINS51742.2021.9524217 ----------------------------------------------------------- Funding Information: This study was supported by the TRUST4IoE project of the Programa Estatal de Proyectos de I+D de Generación de Conocimiento of the Spanish government (grant number PID2019-104065GA-I00). Sergio Trilles has been funded by the postdoctoral Juan de la Cierva fellowship programme of the Spanish Ministry for Science and Innovation (IJC2018-035017-I). 978-1-6654-3156-9/21/$31.00 ©2021 IEEE Publisher Copyright: © 2021 IEEE.